Assessment and management of respiratory function in patients with Duchenne muscular dystrophy: current and emerging options - LoMauro A; D'Angelo MG; Aliverti A (Dove Medical Press, 2015)
Antonella LoMauro,1 Maria Grazia D’Angelo,2 Andrea Aliverti1 1Department of Electronics, Information and Bioengineering, Politecnico di Milano, Milan, 2IRCCS Eugenio Medea, Bosisio Parini, Italy Abstract: Duchenne muscular dystrophy (DMD) is an X-linked myopathy resulting in progressive weakness and wasting of all the striated muscles including the respiratory muscles. The consequences are loss of ambulation before teen ages, cardiac involvement and breathing difficulties, the main cause of death. A cure for DMD is not currently available. In the last decades the survival of patients with DMD has improved because the natural history of the disease can be changed thanks to a more comprehensive therapeutic approach. This comprises interventions targeted to the manifestations and complications of the disease, particularly in the respiratory care. These include: 1) pharmacological intervention, namely corticosteroids and idebenone that significantly reduce the decline of spirometric parameters; 2) rehabilitative intervention, namely lung volume recruitment techniques that help prevent atelectasis and slows the rate of decline of pulmonary function; 3) scoliosis treatment, namely steroid therapy that is used to reduce muscle inflammation/degeneration and prolong ambulation in order to delay the onset of scoliosis, being an additional contribution to the restrictive lung pattern; 4) cough assisted devices that improve airway clearance thus reducing the risk of pulmonary infections; and 5) non-invasive mechanical ventilation that is essential to treat nocturnal hypoventilation, sleep disordered breathing, and ultimately respiratory failure. Without any intervention death occurs within the first 2 decades, however, thanks to this multidisciplinary therapeutic approach life expectancy of a newborn with DMD nowadays can be significantly prolonged up to his fourth decade. This review is aimed at providing state-of-the-art methods and techniques for the assessment and management of respiratory function in DMD patients. Keywords: DMD, spirometry, respiratory muscles, cough device, NIV, steroids, idebenone, respiratory function, lung volume recruitment, scoliosis, spinal fusion, mdx, GRMD